Doors open - Rankin, Ian (Little, Brown and Co., 2010)
Three friends descend upon an art auction and concoct a plan to "liberate" several paintings from the National Gallery. As enterprising girlfriends, clever detectives, a crime boss, seductive auctioneers and a Hell's Angel named Hate enter the picture, this fast-paced story of second guesses and double crosses keeps changing the picture.